2019
DOI: 10.1073/pnas.1911024116
|View full text |Cite
|
Sign up to set email alerts
|

Neogenin-1 distinguishes between myeloid-biased and balanced Hoxb5 + mouse long-term hematopoietic stem cells

Abstract: Hematopoietic stem cells (HSCs) self-renew and generate all blood cells. Recent studies with single cell transplants and lineage tracing suggest that adult HSCs are diverse in their reconstitution and lineage potentials. However, prospective isolation of these subpopulations has remained challenging. Here, we identify Neogenin-1 (NEO1) as a unique surface marker on a fraction of mouse HSCs labeled with Hoxb5, a specific reporter of long-term HSCs (LT-HSCs). We show that NEO1+Hoxb5+ LT-HSCs expand with age and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 82 publications
2
40
0
Order By: Relevance
“…Compared to young adult mice, elderly mice display a significant increase in the number of pHSCs (~ 17-fold for CD34 − LSK cells, [ 27 ] ~ 15-fold for LSK-CD48 − CD150 + , ~ 12-fold for CD34 − LSK-CD48 − CD150 + EPCR + , [ 58 ] ~ 5-fold for SP-LSK [ 52 ]and ~ 10-fold for CD34 − LSK-CD48 − CD150 + FLK2 − ) [ 59 ]. Nevertheless, transplantation studies suggested that the LT-ML HRC of the unpurified BM cells isolated from old mice is increased by only ~ twofold compared to young mice, which is consistent with the ~ 2-fold increase in functional HSCs determined by standard serial dilution and competitive transplantation assays [ 27 , 60 ].…”
Section: Can the Same Markers For Analysis Of Young Hscs Be Used For mentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to young adult mice, elderly mice display a significant increase in the number of pHSCs (~ 17-fold for CD34 − LSK cells, [ 27 ] ~ 15-fold for LSK-CD48 − CD150 + , ~ 12-fold for CD34 − LSK-CD48 − CD150 + EPCR + , [ 58 ] ~ 5-fold for SP-LSK [ 52 ]and ~ 10-fold for CD34 − LSK-CD48 − CD150 + FLK2 − ) [ 59 ]. Nevertheless, transplantation studies suggested that the LT-ML HRC of the unpurified BM cells isolated from old mice is increased by only ~ twofold compared to young mice, which is consistent with the ~ 2-fold increase in functional HSCs determined by standard serial dilution and competitive transplantation assays [ 27 , 60 ].…”
Section: Can the Same Markers For Analysis Of Young Hscs Be Used For mentioning
confidence: 99%
“…The expression of several megakaryocyte–platelet markers, such as CD150 [ 31 ], CD41 [ 71 ], CD61 [ 72 ] and Vwf, [ 68 ] are increased in aged HSCs. In addition, Neogenin-1 (NEO1), a multifunctional transmembrane receptor, is also increased in aged HSCs [ 59 ]. By adding such markers to the well-defined pHSC panels, along with transplantation functional studies, several labs were able to largely isolate My-bi HSCs (CD150 hi , CD41 + , CD61 + , c-Kit hi , Vwf int or Neo1 + ) from Bala-HSCs (CD150 lo , CD41 − , CD61 − , c-Kit Int , Vwf lo or Neo1 − ) [ 71 , 73 ].…”
Section: Increase In Lineage-biased Hscs and Functionally Defective Hmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the well-established HSC immunophenotypes, lineage - Sca-1 + c-Kit + (LSK), endothelial protein C (EPCR) ( 8 ), and the SLAM family proteins ( 9 ) used for the isolation of phenotypic hematopoietic stem and multipotent progenitors (HSPCs), others have been described to reflect HSC function by enriching for distinct lineage bias upon transplantation. Recently, Neogenin-1 (NEO1) was identified to distinguish NEO1 + HSCs primed toward myelopoiesis at the cost of lymphopoiesis from NEO1 - HSCs that show a balanced differentiation into both myelopoiesis and lymphopoiesis ( 10 ). NEO1 + Hoxb5 + HSCs expand with age while NEO1 - Hoxb5 + HSC counts remain unchanged as in young mice.…”
Section: Cellular Heterogeneity In Early Hematopoiesis and The Bm Nicmentioning
confidence: 99%
“…Neo1 can modulate cytoskeletal activities and can function as a co-receptor for bone morphogenetic proteins (BMPs) 40 , 41 . However, the functional role of Neo1 or its ligands such as Ntn1 in HSC biology remains uncertain 1 , 42 . Here, we identify Ntn1–Neo1 signalling as an important regulator of HSC quiescence.…”
Section: Introductionmentioning
confidence: 99%